Status of Selinum spp. L. a Himalayan Medicinal Plant in India: A Review of Its Pharmacology, Phytochemistry and Traditional Uses - Srivastava, Ravi P.; Dixit, Pooja; Singh, Lav; Verma, Praveen C.; Saxena, Gauri (Current Pharmaceutical Biotechnology, 2018)
There is a growing trend of herbal medicines in India as well as other parts of the world. The use of herbal medicines alone or alongside prescription drugs for disease management is quite common now. We hereby carry out a review of dominant species of Selinum mainly S. vaginatum C.B. Clarke and S. wallichianum (DC.) Raizada & H.O. Saxena which are potent source of herbal medicine and whose potential is still not exploited. They are found in Northern Himalayas in the states of Kashmir, Himachal Pradesh and Uttarakhand in India, and also distributed in adjoining countries like China, Nepal, and West Pakistan. It is a perennial, primitive, high altitude, therapeutic herbal plant belonging to family Apiaceae (Umbelliferae) traditionally used for various diseases like epilepsy, seizures, and hysteria, etc. The aim of this review was to provide a summary on botanical characterization, traditional uses, phytochemistry and pharmacological activity of Selinum spp. The available information will be further tapped for commercial use of this plant without endangering its status. Based on the available evidence on the species pharmacology and chemistry, we highlight in which their therapeutic potential can be properly harnessed for possible integration into the country's healthcare system and be further passed on globally.
Keywords: volatile oil